2003
DOI: 10.3998/ark.5550190.0004.e11
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition reactions of porphyrins

Abstract: Adequately substituted porphyrins can participate in pericyclic reactions as dienes, dienophiles, dipolarophiles and as 1,3-dipoles. They also show interesting dipolar 1,5-electrocyclizations and cheletropic reactions with carbenes. All these different types of reactivity have been exploited in order to synthesize new potential biologically active porphyrin derivatives, mainly chlorins and bacteriochlorins. This paper reviews the most recent works where porphyrins have participated in pericyclic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 15 publications
(16 reference statements)
1
33
0
Order By: Relevance
“…The optimized geometries of OP derivatives obtained from DFT calculations are illustrated in Figure 2 . These systems exist in two atropisomeric forms P and M (Sprutta and Latos-Grazyński, 2001 ; Flemming and Dolphin, 2002 ; Pushpan et al, 2002 ; Silva et al, 2002a , b ; Cavaleiro et al, 2003 ; Hata et al, 2006 ; Tanaka and Osuka, 2016 ). P and M isomeric forms are the mirrors images of each other, which do not show any distinction in electronic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized geometries of OP derivatives obtained from DFT calculations are illustrated in Figure 2 . These systems exist in two atropisomeric forms P and M (Sprutta and Latos-Grazyński, 2001 ; Flemming and Dolphin, 2002 ; Pushpan et al, 2002 ; Silva et al, 2002a , b ; Cavaleiro et al, 2003 ; Hata et al, 2006 ; Tanaka and Osuka, 2016 ). P and M isomeric forms are the mirrors images of each other, which do not show any distinction in electronic properties.…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of sapphyrins and expanded porphyrins have attracted the interest of researchers attributed to their diverse applications in materials science (Sprutta and Latos-Grazyński, 2001 ; Flemming and Dolphin, 2002 ; Pushpan et al, 2002 ; Silva et al, 2002a , b ; Cavaleiro et al, 2003 ; Hata et al, 2006 ; Tanaka and Osuka, 2016 ). The defining feature of these macrocycles is the presence of a larger internal cavity as compared to those present in natural tetrapyrroles.…”
Section: Introductionmentioning
confidence: 99%
“…It was aimed to look for how the acid used, the power applied, the reaction time, the reactants concentration and lastly, how the closed vessels system can affect the yield in the synthesis of TPP. This porphyrin was chosen because it is the most simple one and it is being used in a wide range of chemical studies mainly related to the reactivity and functionalization of the macrocycle [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In very recent years, Diels-Alder 4 and 1,3-dipolar cycloaddition (1,3-DC) 5 reactions have been intensively exploited as convenient means for the atom economical transformation of porphyrins into chlorins, as well as the bis-adduct bacteriochlorins and isobacteriochlorins. 6 Various types of condensed five-membered rings have been built up from reactions of porphyrins with azomethine and carbonyl ylides, nitrones and diazomethane. 6 Previous work from these laboratories demonstrated that the 1,3-DC of sugar nitrones to porphyrins is a convenient strategy for the introduction of one-or two-fused isoxazolidine rings each one bearing a carbon-linked pyranoside or furanoside residue.…”
mentioning
confidence: 99%
“…6 Various types of condensed five-membered rings have been built up from reactions of porphyrins with azomethine and carbonyl ylides, nitrones and diazomethane. 6 Previous work from these laboratories demonstrated that the 1,3-DC of sugar nitrones to porphyrins is a convenient strategy for the introduction of one-or two-fused isoxazolidine rings each one bearing a carbon-linked pyranoside or furanoside residue. 7 The incorporation of sugar residues into substrates endowed with a well established biological activity may improve their bioavailability while retaining their activity and selectivity.…”
mentioning
confidence: 99%